Alkali metal salts of 4‐hydroxybenzoic acid: a structural and educational study. Issue 7 (9th June 2021) - Abrahams, Brendan F.; Commons, Christopher J.; Hudson, Timothy A.; Sanchez Arlt, Robin; White, Keith F.; Chang, Michael; Jackowski, John J.; Lee, Matthew; Lee, Shang X.; Liu, Harrison D.; Mei, Bill M.; Meng, Joshua E.; et al.
Abstract : Although 4‐hydroxybenzoic acid (H2 hba) is a relatively simple organic molecule, it displays remarkable coordinative flexibility in its reactions with alkali metal hydroxides, forming ionic networks containing the dianion (hba 2− ), the monoanion (Hhba − ) or the neutral acid species (H2 hba). A common feature of the structures of the lattices is their layered arrangement: alternating hydrophilic layers made up of closely packed metal–oxygen polyhedra are separated by the hydrophobic nonpolar components of the hydroxybenzoate linking units. Abstract : As part of an educational exercise designed to introduce school students to the technique of single‐crystal X‐ray diffraction and enhance their understanding of primary and secondary bonding, a group of nine secondary school students was given the opportunity to prepare new compounds and to solve and refine data collected on the crystalline materials they had prepared. Their investigation of the alkali metal salts of 4‐hydroxybenzoic acid (H2 hba) yielded nine new compounds and their structures are described in this article. Whilst the salts might be expected to have similar atomic arrangements, there are significant differences in their structures. Although H2 hba is a relatively simple organic molecule, it displays remarkable coordinative flexibility, forming ionic solids containing the uncharged molecule, the monoanion Hhba − or the dianion hba 2− . A common feature of the structures is their layered arrangement: alternating hydrophilic layers made up of closely packed metal–oxygen polyhedra separated by the hydrophobic component of the hydroxybenzoate linking units. Close packing of these units seems to be a dominant influence in determining the overall structure. The hydroxybenzoate units are usually both parallel and antiparallel with their immediate neighbours, with packing that can be edge‐to‐face, face‐to‐face or a mixture of the two. Hydrogen bonding plays a key role in the structure of most compounds and a short strong hydrogen bond (SSHB) is observed in two of the networks. The compounds of 4‐hydroxybenzoic acid, C7 H6 O3, described here are: poly[di‐μ‐aqua‐μ‐4‐oxidobenzoato‐dilithium], [Li2 (C7 H4 O3 )(H2 O)2 ] n, 1, poly[triaqua‐μ‐4‐oxidobenzoato‐dilithium], [Li2 (C7 H4 O3 )(H2 O)3 ] n, 2, poly[μ‐4‐hydroxybenzoato‐lithium], [Li(C7 H5 O3 )] n, 3, catena ‐poly[4‐hydroxybenzoate [[diaquasodium]‐di‐μ‐aqua]], [Na(H2 O)4 ](C7 H5 O3 ) n, 4, poly[di‐μ‐aqua‐aqua‐μ‐4‐hydroxybenzoato‐potassium], [K(C7 H5 O3 )(H2 O)3 ] n, 5, poly[μ‐aqua‐μ‐4‐hydroxybenzoato‐potassium], [K(C7 H5 O3 )(H2 O)] n, 6, poly[aqua‐μ‐4‐hydroxybenzoato‐rubidium], [Rb(C7 H5 O3 )(H2 O)] n, 7, poly[aqua‐μ‐4‐hydroxybenzoato‐caesium], [Cs(C7 H5 O3 )(H2 O)] n, 8, poly[[μ‐aqua‐aqua(μ‐4‐hydroxybenzoato)(4‐hydroxybenzoic acid)sodium] monohydrate], [Na(C7 H5 O3 )(C7 H6 O3 )(H2 O)2 ]·H2 O n, 9, poly[[(μ‐4‐hydroxybenzoato)(μ‐4‐hydroxybenzoic acid)rubidium] monohydrate], [K(C7 H5 O3 )(C7 H6 O3 )]·H2 O n, 10, and poly[[(μ‐4‐hydroxybenzoato)(μ‐4‐hydroxybenzoic acid)rubidium] monohydrate], [Rb(C7 H5 O3 )(C7 H6 O3 )]·H2 O n, 11 .